Legality of The Use of Water Birth Methods in Childbirth Practices in Indonesia - Andryawan Andryawan; Aryanti Agripina Winata; Kearen Elvira Naftali; Marcia Gladys Rumambi (Journal of Research in Social Science and Humanities, 2025)
Doctors, as one of the main providers of health services to the community, play a very central role because they are directly involved in the provision of health services and the quality of those services. The main foundation for doctors to be able to perform medical procedures on patients is their knowledge, technology, and competence. The decline in public trust in doctors, as well as the increasing number of legal claims filed today, are often associated with failures in the healing efforts undertaken by doctors. These conflicts are triggered by patients' dissatisfaction with doctors in carrying out treatments or practicing their medical profession. In providing care, every doctor must uphold medical ethics, which determine the integrity of this profession. This raises the issue of the legality of using the water birth method in childbirth procedures performed by obstetricians and gynecologists in Indonesia and the role of the Medical Ethics Honorary Council (MKEK) in addressing this issue. The method used in this study is a normative method obtained through library research, supported by data from interviews with the West Jakarta IDI. The research findings indicate that the water birth method is not yet recommended for use in medical practice in Indonesia. Neither the IDI nor the Indonesian Medical College has recognized this method. When an obstetrician-gynecologist uses this method, the doctor in question may be categorized as having violated medical professional discipline and medical ethics. The Medical Ethics Council (MKEK) of the Indonesian Medical Association (IDI) will take action against any doctor found to have violated medical ethics. The enforcement of medical ethics by the MKEK IDI is more of a form of guidance for doctors to better understand and adhere to the code of medical ethics.